Special education and contemporary theater:: the creative process of De Lagarta à Borboleta, a flight through diversity and autonomy in relational practices (DAPesquisa, 2021)
This text proposes an account of the creative process De Lagarta a Borboleta with people with disabilities in the (APAE) Association of Parents and Friends of the Exceptional in Ouro Preto - MG. Thus, the article aims to contribute to the field of studies about the teaching and practice of Contemporay Theater in contexts of Special Education; in addition to focusing on the collaborative creation experience lived in theater practices developed by a group of interns from the Bachelor's degree in Performing Arts - UFOP / MG. Finally, it seeks to understand theater as a language and a path for the construction of knowledge linked to other knowledge, in an interdisciplinary context.
Keywords: Drama in education; People with disabilities and the performing arts; Artists with disabilities; Special education